(untitled) (Revista Nacional de Odontología, 2016)
Pain in the muscles of mastication, limited opening, asymmetric jaw movement, and sounds in the TMJ, among others symptoms are some clinical characteristics of temporomandibular disorders (TMD). It is a complain in subjects of both sexes, different ages and occlusal conditions. Objective: To determine the most frequent pathology and temporomandibular symptomatology in elderly edentulous patients. Materials and Methods: 30 consecutive subjects,25 female and five men older than 65 ys (70.8±5.7), all edentulous and wearing prosthesis were recruited according inclusion criteria. Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) questionnaire and examination form were applied to determine axis I temporomandibular disorders and symptomatology, and axis II behavioral conditions. Results:From the total sample (30), 28 subjects (93%) presented at least one or more symptoms of TMD but not necessary were diagnosed with a specific pathology. According axis I, two subjects presented pathology corresponding to group 1 (7%), five to group 2 (23%), and 11 to group 3 (37%). Respect to RDC/TMD axis II, 20% of the sample showed some chronic pain degree, and 73% had some tendency to depression. Conclusion: Elderlyedentulous examined showed a high frequency of temporomandibular symptoms. This situation is not necessarily an indicator of a dysfunctional pathology diagnosed under the context of the RDC / TMD. The high index of depression tendency, not only is due to TMD, and could be a result of edentulism or another situation.